2018
DOI: 10.1158/2159-8290.cd-18-0432
|View full text |Cite
|
Sign up to set email alerts
|

A Digital RNA Signature of Circulating Tumor Cells Predicting Early Therapeutic Response in Localized and Metastatic Breast Cancer

Abstract: The multiplicity of new therapies for breast cancer presents a challenge for treatment selection. We describe a 17-gene digital signature of breast circulating tumor cell (CTC)-derived transcripts enriched from blood, enabling high-sensitivity early monitoring of response. In a prospective cohort of localized breast cancer, an elevated CTC score after three cycles of neoadjuvant therapy is associated with residual disease at surgery ( = 0.047). In a second prospective cohort with metastatic breast cancer, base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 47 publications
1
82
0
Order By: Relevance
“…In general, most of these studies have been performed in low numbers of patients and the prognostic value of these gene signatures will have to be tested in larger clinical trials. In localized and metastatic breast cancer, a recent analysis identified a 17-gene digital signature in CTCs that was associated with residual disease at surgery and with treatment response [121]. Another study developed an assay based on eight CTC-derived transcripts in prostate cancer that was predictive of abiraterone response in the metastatic setting and of early dissemination in localized disease [122].…”
Section: Clinical Value Of Ctcsmentioning
confidence: 99%
“…In general, most of these studies have been performed in low numbers of patients and the prognostic value of these gene signatures will have to be tested in larger clinical trials. In localized and metastatic breast cancer, a recent analysis identified a 17-gene digital signature in CTCs that was associated with residual disease at surgery and with treatment response [121]. Another study developed an assay based on eight CTC-derived transcripts in prostate cancer that was predictive of abiraterone response in the metastatic setting and of early dissemination in localized disease [122].…”
Section: Clinical Value Of Ctcsmentioning
confidence: 99%
“…Similarly, signatures derived through scRNA-seq of a chemoresistant subpopulation of TNBCs did not show overlap with any of our normal cell clusters (Kim et al, 2018). Genes in the breast cancer-specific RNA signature that detect circulating tumor cells did not show overlap with any specific cluster, but genes like PIP, CXCL14, and SFRP2, which are markers of circulating tumor cells are enriched in clusters 4, 6 and 12, respectively (Kwan et al, 2018). Thus, genomic aberrations and transcription programming rather than cell-of-origin may have given rise to drug resistant and metastatic subpopulations of tumor cells.…”
Section: Gene Signatures Of Epithelial Clusters and Their Relevance Tmentioning
confidence: 63%
“…In MBC patients with ER-positive primary tumors, it has been proposed that lack of ER expression in CTCs could be a possible mechanism of resistance to endocrine therapy (50), and that is also associated to increased migration and invasion (51). In MBC patients with ER-positive disease, the presence of ESR1 mutations in CTCs is one of the diverse mechanisms of acquired endocrine drug resistance and could explain failure to suppress ER signaling within CTCs after 3 weeks of endocrine therapy (52). Another study has shown that in MBC ESR1 mutations were absent in primary tumor tissue samples and were detected only in metastases obtained after CTC characterization (53).…”
Section: Discussionmentioning
confidence: 99%